Chemosensory event-related potentials in early blind humans - Cuevas, I; Plaza, P; Rombaux, P; Mouraux, A; Delbeke, J; Collignon, O; De Volder, A G; Renier, L (B-ENT (Leuven), 2011)
While the effects of early visual deprivation on auditory and tactile functions have been widely studied, little is known about olfactory function in early blind subjects. The present study investigated the potential effect of early blindness on the electrophysiological correlates of passive odour perception. Event-related potentials (ERPs) were recorded in eight early blind humans and eight sighted controls matched for age, sex and handedness during olfactory stimulation with 2-phenyl ethyl alcohol and trigeminal stimulation with CO2 Latencies, amplitudes and topographical distributions were analysed. As expected, the olfactory and trigeminal ERP components showed normal latencies, amplitudes and topography in both groups. Olfactory stimuli generated responses of smaller amplitude than those observed in response to trigeminal stimulation. In addition, ERP analyses did not reveal any major difference in electrocortical responses in occipital areas in early blind and sighted subjects. These results suggest that passive olfactory and trigeminal stimulation elicit the same electrophysiological responses in both groups, confirming that the neurophysiological correlates of the cross-modal compensatory mechanisms in early blind subjects do not appear during passive olfactory and trigeminal perception.